Luminescent Copper(I) complexes as promising materials for the next generation of energy-saving OLED devices - Leandro P. Ravaro; Kassio P. S. Zanoni; Andrea S.S. de Camargo (Energy Reports, 2020)
The increasing demand for electrical energy by a longer living and increasing population justifies the search for new, more efficient lighting systems. In this context, organo-metallic compounds have been largely investigated as efficient materials for organic light emitting diodes (OLEDs). Special interest has been demonstrated for neutral copper(I) complexes due to their high emission quantum efficiency and fast photoluminescence response time. In particular, Cu(I) complexes that present thermally activated delayed fluorescence (TADF) are one of the most promising materials for the next generation of lighting devices. In this work, we present an overview of the development of OLEDs, by comparing the mechanisms and efficiencies of different complexes and discussing the reasons why Cu(I) complexes have potential to be one of the most efficient alternatives for energy saving in lighting.
Keywords: 330; Light emitting devices; OLED; TADF; Cu(I) complexes